Polymorphonuclear leukocyte mediated oxidative inactivation of alpha-1-proteinase inhibitor: Modulation by nitric oxide - Mir, Mohammad Muzaffar (Springer India, 2005)
Alpha-1-proteinase inhibitor activity was studied in presence of resting and activated polymorphonuclear leucocytes. Four different agonists; phorbol myristic acetate, N-formyl-methionyl-leucyl-phenylalanine, opsonised zymosan and arachidonic acid decreased the inhibitor activity by 23.3%, 20%, 12% and 16.6^ respectively. The inhibitor activity was protected by using various free radical scavengers. Catalase and superoxide dismutase both restored activity by about 18%, mannitol by 13% and sodium azide by 17.3%. The inhibitor activity was also protected significantly by pretreatment of polymorphs with L-Arg, a precursor of nitric oxide, before activation. L-Arg was also observed to suppress the generation of superoxide and hydroxyl radical appreciably. The nitric oxide synthase inhibitor, aminoguanidine drastically inhibited the nitrite release and reversed the protection offered by L-Arg to the inhibitor activity. Our results indicate a multifactorial nature of the inactivation process, the culprit species being superoxide, hydrogen peroxide, hydroxyl radical and hypohalides. Nitric oxide seems to scavenge the superoxide radical directly after its formation rather than inhibiting its generation by NADPH oxidase as was believed earlier.